Answer:
144.44
Step-by-step explanation:
C = 2 x π x r . C = 2 x 3.14 x 23 = 144.44
Answer:
A)
y^2-6y = 0
or, y(y-6) = 0
or, y = 0 or y = 6
B)
n^2+5n+7 = 7
or, n^2+5n+7-7 = 7-7 ( Subtracting 7 from both sides)
or, n^2+5n = 0
or, n(n+5) = 0
or, n=0 or n= -5
C)
2t^2-14t+3 = 3
or, 2t^2-14t = 0
or, 2t(t-7) = 0
or, t=0 or t=7
D)
1/3x^2+3x-4 = -4
or, 1/3x^2+3x = 0
or, 1/3x(x+9) = 0
or, x=0 or x= -9
E)
Zero is a common solution to each of the equations. This is because each of the equations had a variable outside the parenthesis with an operation of multiplication.
THANK YOU FOR READING.
Answer:
{x,y}={8,5}
Step-by-step explanation:
12x + 12y = 156 4x + 6y = 62
Answer:
b
Step-by-step explanation:
Answer:
see below
Step-by-step explanation:
some of your answers that you currently have are wrong, I'll note those mistakes below
- when factoring (ie 5x+15) only factor out things that can divide both numbers into a whole number ratio
5x+15 = 5(x+3), not (x+3)(x+5)
ie ![\frac{10x^2+20x}{x+2}](https://tex.z-dn.net/?f=%5Cfrac%7B10x%5E2%2B20x%7D%7Bx%2B2%7D)
we see that 10x can divide the numerator in a whole number ratio
= 10x(x+2), not (x+2)(x+10)
second mistake: the first binomial expansion is incorrect.
you have the expansion formula right, but you added terms wrong, go look at it again
3. x^2+3x+2/ x^2+5x+6
(x+1)(x+2)/(x+3)(x+2)
(x+1)/(x+3)
4. (x^2+6x+8)/(x^2-16)
(x+4)(x+2)/(x+4)(x-4)
(x+2)/(x-4)
5. we can't simplify that any more, x and y are different variables so therefore we cannot cross out stuff on numerator and denominator
6. (x^4y^6)^2
(x^4y^6)(x^4y^6) = ![x^8y^{12}](https://tex.z-dn.net/?f=x%5E8y%5E%7B12%7D)
remember that (x^a)(x^b) = x^(a+b)
or remember that (x^a)^b = x^ab